Enhancing Sales Performance Through Human Resource Interventions: Training, Coaching, and Competency Development in Consultative Selling (A Practical Study at Telkom Yogyakarta) - Sakti, Hanung Satria; Palupi, Majang (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the implementation of consultative selling strategies in the sales of IndiBiz products at Telkom Yogyakarta, focusing on the role of the Human Resources (HR) department in supporting the development of sales team competencies. The research employs a qualitative approach through in depth interviews, observations, and documentation, with participants consisting of the HR Manager, Sales Supervisor, and members of the sales team. The findings indicate that the role of the HR department is crucial, not only as a provider of training but also as a change agent that facilitates the transformation of the sales mindset from transactional selling to a consultative approach. The inhibiting factors identified include competency gaps, low self confidence among sales staff, an incentive system that emphasizes quantity over the quality of interactions, and the price sensitive characteristics of the MSME market in Yogyakarta. Support in the form of training, coaching, monitoring, and evaluation has been proven to enhance sales competencies, although consistent follow up is still required for effectiveness in practice. With continuous improvements in training, incentive systems, and the utilization of CRM, the consultative selling strategy has the potential to increase customer value and drive sustainable sales growth for IndiBiz.